GAMBARAN PENGETAHUAN DAN SIKAP WANITA PEKERJA SEKSUAL TIDAK LANGSUNG DI HOTSPOT JALAN TUANKU TAMBUSAI KECAMATAN SUKAJADI PEKANBARU TERHADAP PAP SMEAR DAN INSPEKSI VISUAL ASETAT SEBAGAI DETEKSI DINI KANKER SERVIKS - Tilusari, Shinta Puja; ", Suyanto; Fidiawati, Wiwit Ade (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Cervical cancer is the third most frequent cancer in women in Indonesia. Cervical cancer is a disease that may impact to many psychosocial condition for the patient. In Indonesia found about 40.000 new case of cervical cancer. Indirect female sex worker are in high risk for having cervical cancer. The aim of the research is to describe indirect female sex worker knowladge and attitude at Tuanku Tambusai Street in Pekanbaru toward Pap smear and Visual Inspection with acetid acid as cervical cancer screening. The descriptive methode was used with in 35 persons that was taken under total sampling technique through direcly interview by using quetionnaire. The result of study from 35 repondents, 32 repondents have bad knowladge with 91,43%, 3 respondents have moderate knoeladge with 8,57%, and none of respondents has good knowladge. On attitude quesionnaire, 26 respondents have negative attitude 74,29%, 9 respondents have positif attiude with 25,71%. The conclusion is indirect female sex worker at Tuanku Tambusai Street in Pekanbaru have bad knowladge and negative attitude toward Pap smear and Visual Inspection with acetic acid as cervical cancer screening Keywords: Knowladge, attitudes, Indirect female sex worker, Pap smear and IVA.